Desenvolvimento e testagem de uma bateria de avaliação informatizada de atenção, memória e controle inibitório em crianças do Ensino Fundamental I - Lellis, Vera Rocha Reis (2017)
Neuropsychological assessment studies processes interrelated issues, such as attention, memory, and inhibitory control. Attention can be understood as a set of neural processes that allow adequate selection of information from the environment, and therefore guide adaptive responses. Memory, however, is considered a complex and multiple system combined with coding arrangements or subsystems that allow the storage and retrieval of brain information. The executive process component, inhibitory control refers to the ability to withstand a first impulse and to control behavior or thinking. The objective of this study was to develop and test a battery of computerized evaluation of attention, memory and inhibitory control in children of Elementary School and to evaluate how these functions develop over the school years. 85 children aged 6 to 11 years, from a private school in a city in the state of SP, were participating in this study. Traditional instruments (pencil-paper tests) and computerized instruments were used for evaluation. They were used as instruments: Wechsler Scale of Intelligence (WISC- IV) Subtest: Digit Span and Letter – Number Sequencing; Wechsler Abbreviated Scale of Intelligence (WAIS), subtest: Vocabulary and Matrix Reasoning; Attention by Cancelling Test (TAC); Test of Tracks. For behavioral evaluation there were: Behavioral Scale (CBCL/6-18) and Functional Instrument (IFERI) applied to parents. The following tests were used for the school teachers: Behavioral Scale (TRF/6-18); Functional Instrument (IFERI). Multivariate anovas were used to compare the results according to school series and person correlation analyzes between the indices of the instruments to evaluate their possible associations. Results showed the children presented satisfactory index in all traditional tests (pencil and paper). On the other hand, the computerized automatic and voluntary attention tests show a decrease in reaction time (RT) as a result of the school year. Older children showed better targeting of voluntary and automatic attention. That fact can be attributed to maturity of the attentional system. Another observed factor was that the TR for the condition where the track and target come in the same position (Ipsolateral) tends to be smaller than the condition in which the track come on opposite sides (Contralateral). It is possible to observe that the RT in the 800 ms range are smaller than the RT for 100, 300 ms intervals because the children have more time to direct the attention. In the correlation of computerized tests, reduced RTs and hits grow as children grow older and study more advanced school series. In the Go X No-Go Tests RTs increase because older children are more capable to wait the correct answers then younger. That shows older children have a better inhibitory control then younger. Additionally, older children were faster than the youngers to begin and solve the memory tests. In the correlations between the computerized tests and the IFERI we can see that parents come with more problems than teachers. Although the teachers report fewer problems, it is verified that the difficulties perceived through the instruments are more consistent with the performance of the children in the tests. For those reasons, it is possible to say the proposed computerized tests help to evaluate cognitive abilities in the human developed process.